Math

step 1:
x = integral(from 0 to v) dv/(z^2-v^2)

step 2:
x = 1/2z ln((q+v)/(q-v))

How do you get from step 1 to step 2 ?

  1. 👍 0
  2. 👎 0
  3. 👁 53
asked by Anthony
  1. The indefinite integral of
    dv/(z^2-v^2),
    with z being a constant, is
    [1/(2z)]log[(z+v)/(z-v)]
    Evaluate that at v=v' and subtract the value for v=0, to get the definite integral.

    The method of partial fractions can used to get the integral. It involves rewriting 1/[(z^2-v^2} as
    [1/(2z)][1/(z+v) - 1/(z-v)]

    1. 👍 0
    2. 👎 0
    posted by drwls

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

    asked by Anonymous on October 25, 2018
  2. ALGEBRA HELP

    When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

    asked by cv on October 21, 2013
  3. Geometry

    A parabola has a focus of F(2,8.5) and a directrix of y=9.5. The point P(x,y) represents any point on the parabola, while D(x,9.5) represents any point on the directrix. Maria was asked to use the distance formula to write an

    asked by lilbaby on December 4, 2018
  4. Chemistry

    In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step

    asked by Haley on April 7, 2015
  5. trig sub question

    Hello, I have a question concerning trigonometric substitution. let's say we have integral of dx/sqrt(9x^2 + 4), so after doing a few steps we have: 2/3 integral of sec0/sqrt((2tan0)^2 + 4*) d0 (the * is for later on) the next

    asked by Tom on February 22, 2013
  6. Algebra help

    f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is from my book: step 1: 0=x^3-4x^2-x+4 step 2: 0=x^2(x-4)+(-1)(x-4) step 3: 0=(x^2-1)(x-4) I know how to solve once I get to step 3, but in step 2, I don't know what

    asked by Claure on June 16, 2009
  7. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

    asked by oscar on September 4, 2015
  8. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

    asked by oscar on September 4, 2015
  9. aps

    There are 26 step on flpor at the time saad comes down two step imad step up one step When will tyey meet at what step?

    asked by sayed on January 23, 2017
  10. Math

    In which step is the error? Step 1: Let x = 1 and y = 1. Step 2: By substitution xy = y^2. Step 3: Multiplying both sides by -1, -xy= -y^2. Step 4: Adding x^2 to both sides, x^2-xy=x^2-y^2. Step 5: Factoring, x(x-y)=(x+y)(x-y).

    asked by Hannah on February 1, 2016
  11. Quick math help

    In which step below does a mistake first appear in simplifying the expression? 0.5(-12c+6)-3(c+4)+10(c-5) Step 1: -6c+3-3(c+4)+10(c-5) Step 2: -6c+3-3c-12+10(c-5) Step 3: -6c+3-3c-12+10c-50 Step 4: 7c-41 Please help me!!! Thank

    asked by Anonymous on December 11, 2013

More Similar Questions